Analisis Manajemen Pengelolaan Zakat dalam Meningkatkan Kesejahteraan Mustahik di SMKN Pringkuku Pacitan - Yuntoro Tri Pranoto; Mokhamad Choirul Hudha (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The effectiveness of zakat management within the educational sector plays a crucial role in improving mustahik welfare. This study aims to analyze the management of zakat by the School Zakat Management Unit (UPZ) at SMKN Pringkuku Pacitan in enhancing the well-being of its beneficiaries. Utilizing a descriptive qualitative approach, data were gathered through interviews, direct observations, and documentary reviews. The findings reveal that the zakat management mechanism has been structured systematically, encompassing collection, distribution, and mustahik classification based on the eight categories of asnaf. Specifically, professional zakat (zakat profesi) is collected via a 2.5% monthly salary deduction from civil servant (PNS) and government employee (PPPK) staff, while zakat fitrah is accumulated from all teachers, staff, and students. The allocated zakat funds are regularly distributed to underprivileged students, orphans, and the community residing around the school environment. This financial intervention is proven to yield a positive impact by supporting educational expenses, fulfilling daily basic needs, and boosting students' learning motivation. The implication of this study emphasizes that the school-based zakat management model holds significant potential to be replicated as an effective social empowerment instrument to secure student welfare.